Identifying Factors Underlying the Decision for Sickle Cell Carrier Screening Among African Americans Within Middle Reproductive Age. Issue 5 (24th March 2018) - Mayo‐Gamble, Tilicia L.; Middlestadt, Susan E.; Lin, Hsien‐Chang; Cunningham‐Erves, Jennifer; Barnes, Priscilla; Jackson, Pamela Braboy
Abstract: Guidelines recommend that African Americans know their sickle cell trait status to inform reproductive health decisions. Few studies have applied a behavioral theory to identify factors associated with sickle cell trait screening to inform intervention targets to increase this behavior. We applied a Sickle Cell Trait Screening Framework to identify factors associated with African Americans' intention to ask for sickle cell trait screening . Participants ( N  = 300), ages 18 to 35, completed a cross‐sectional survey. A three‐step sequential ordinary least squares regression analysis identified factors influencing intention. Results indicated socio‐demographic factors (age, education), knowledge and fear beliefs (screening knowledge, perceived threat), and reasoned action approach (RAA) constructs were associated with intention. RAA constructs influenced intention over knowledge and fear beliefs with an increase in R 2 of .468. Perceived behavioral control was more predictive of intention (β = .576, p  < .001). Attitude and perceived norm also had significant weights (β = .325 and β = .192, both p  < .001, respectively). Findings from this study can inform strategies (e.g., eliminating costs associated with screening, reducing fear of painful tests) to increase sickle cell trait screening among African Americans. Ultimately, more sickle cell carriers will become aware of their trait status and be able to make informed reproductive health decisions.